Pengaruh Etos Kerja terhadap Kinerja Pegawai di PPSDM Aparatur - Zulkifli, Zulkifli (Pusat Pengembangan Sumber Daya Manusia Aparatur, 2023)
ABSTRACT To be able to realize a synergistic relationship between individuals and organizations, organizations must be able to pay attention to the performance patterns of their employees. Employees who are qualified and can produce high performance are employees needed by an organization. A very vital role in realizing the performance of an employee is himself. Employees must have high enthusiasm and work ethic to be able to have a positive impact on their environment. Employees who have noble thoughts about their work can work sincerely. Based on this, this research was carried out with the aim of carrying out a theoretical test regarding the effect of work ethic on the performance of Employees at the PPSDM Aparatur. To examine the relationship between work ethic and employee performance, regression analysis was used by distributing questionnaires to employees at the PPSDM Aparatur. The results of the study found that the process of cultivating a work ethic and the process of realizing employee performance in PPSDM Aparatur became the goals of the organization. The approach used in this study is quantitative with explanative methods, the type of data is quantitative, the sample is determined based on the Slovin method with data collection techniques through questionnaires while data analysis is carried out by conducting descriptive analysis, validity and reliability tests and regression analysis. The research hypothesis is accepted, namely that the more optimal the work ethic is, the more influential it will be on employee performance in PPSDM Aparatur, which means that there is an influence between the work ethic variable and employee performance variables.ABSTRAK Untuk dapat mewujudkan hubungan yang sinergis individu dan organisasi, organisasi harus dapat memperhatikan pola kinerja Pegawainya. Pegawai yang bermutu dan dapat menghasilkan kinerja yang tinggi adalah Pegawai yang dibutuhkan oleh suatu organisasi. Peran yang sangat vital dalam mewujudkan prestasi kinerja seorang Pegawai adalah dirinya sendiri. Pegawai harus memiliki semangat dan etos kerja yang tinggi untuk dapat memberikan pengaruh positif pada lingkungannya. Pegawai yang memiliki pemikiran yang luhur mengenai pekerjaannya dapat bekerja dengan tulus. Berdasarkan hal tersebutlah dilakukan Penelitian ini dengan tujuan untuk melakukan uji teoritik mengenai pengaruh etos kerja terhadap kinerja Pegawai PPSDM Aparatur. Untuk menguji hubungan variabel etos kerja terhadap kinerja Pegawai digunakan analisis regresi dengan menyebar kuesioner pada Pegawai PPSDM Aparatur. Hasil penelitian ditemukan bahwa proses Penanaman Etos Kerja dan proses terwujudnya Kinerja Pegawai di PPSDM Aparatur yang menjadi tujuanorganisasi. Pendekatan yang digunakan dalam penelitian ini yaitu kuantitatif dengan metode explanatif, jenis datanya kuantitatif, sampel ditentukan berdasarkan metode Slovin dengan teknik pengumpulan data melalui angket/kuesioner sedangkan analisis data dengan melakukan analisis dekriptif, uji validitas dan realibilitas serta analisis regresi. Hipotesis penelitian ini diterima yaitu semakin optimal Penanaman Etos Kerja maka semakin berpengaruh terhadap Kinerja Pegawai di PPSDM Aparatur yang berarti terdapat pengaruh antara variabel Etos Kerja terhadap variabel Kinerja Pegawai.